Ultrasound evaluation of intra-osseous cavity: A preliminary study in pig mandibles - Thásia L.D. Ferreira; Andre Luiz F. Costa; Maria José A. Tucunduva; Raul R. Tucunduva-Neto; Elio H. Shinohara; Cláudio F. de Freitas (Journal of Oral Biology and Craniofacial Research, 2016)
Aims: To assess the role of ultrasonography as a possible tool for diagnosis of intra-osseous lesions. Methods: Our sample comprised five macerated pig jaws. The regions of bony crypts of third molars were examined on both sides, totaling 10 examinations. The degrees of difficulty for both ultrasound image visualization and bone translucency were rated by two groups of evaluators (i.e. dental radiologists and physician ultrasonographers). Results: Our results showed that it is possible to detect images of the intra-osseous cavity at a low-degree difficulty by using both radiographic and ultrasonic techniques (46.6% and 43.3%, respectively). However, the crypts were not fully detected by both groups (16.6% and 13.3%, respectively). Conclusions: We concluded that ultrasonography is a useful method for evaluation of intra-osseous lesions in jaws, provided that the cortical bone is thin enough to allow ultrasound waves to pass through.